Airborne Coherent Doppler Wind Lidar measurements of vertical and horizontal wind speeds for the investigation of gravity waves - Witschas, Benjamin; Rahm, Stephan; Wagner, Johannes; Dörnbrack, Andreas (2016)
Gravity waves are well known phenomena in the atmosphere, but there is still a lack of knowledge of their life cycle including excitation, propagation and dissipation mechanisms. In order to investigate these topics, DLR’s coherent Doppler wind lidar system was recently deployed during 3 airborne campaigns on the Falcon F20 research aircraft, namely the GW-LCYCLE I campaign (Kiruna, Sweden, December 2013), the DEEPWAVE campaign (Christchurch, New Zealand, June/July 2014) and the GW-LCYCLE II campaign (Kiruna, Sweden, January/February 2016). In this paper, a case study based on a research flight performed during GW-LCYCLE I is discussed and a method for correcting horizontal wind contribution in the vertical wind retrieval based on ECMWF data is introduced. The remaining systematic error of the retrieved vertical wind is estimated to be less than 10 cm/s. A measurement of a flight leg across the Scandinavian mountain ridge is used to characterize gravity waves during strong forcing conditions. The measured vertical wind reaches amplitudes of larger than ± 3 m/s and horizontal wavelengths of 10 km to 20 km. A comparison with WRF-model calculations shows a quite good representation of the horizontal structure of the vertical wind. The amplitude however is obviously underestimated by a factor of 2 and shows maximum wind speeds of ± 1.5 m/s.